2019
DOI: 10.12681/bgsg.20756
|View full text |Cite
|
Sign up to set email alerts
|

Plagioclase Hosted Melt Inclusion in Hypabyssal Rocks in Torud-Ahmad Abad Magmatic Belt

Abstract: This study investigates for the first time melt inclusions (MI) that are found within fundamental minerals of subvolcanic rocks in Torud-Ahmad Abad magmatic belt. The Torud-Ahmad Abad magmatic belt is situated in south-southeast of Shahrood and belongs to the northern part of central Iran structural zone. Melt inclusions represent liquids that were trapped along growth zones (primary) or healed fractures of mineral phases, which crystallized from the silicate liquid as it cooled. Based on SEM analysis of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This area has similar geochemical characteristics to the studied areas. Based on a recent analysis on the melt inclusions that were hosted within plagioclase phenocrysts in andesite, trachyandesite, basaltic andesite, and dacite, it was found that the crystallized melt inclusions in these rocks exhibited considerable intrasample diversity that relates to petrogenesis and compositional evolution (Yousefi, Papadopoulou, Sadeghian, Wanhainen, & Bark, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This area has similar geochemical characteristics to the studied areas. Based on a recent analysis on the melt inclusions that were hosted within plagioclase phenocrysts in andesite, trachyandesite, basaltic andesite, and dacite, it was found that the crystallized melt inclusions in these rocks exhibited considerable intrasample diversity that relates to petrogenesis and compositional evolution (Yousefi, Papadopoulou, Sadeghian, Wanhainen, & Bark, 2019).…”
Section: Discussionmentioning
confidence: 99%